PENGARUH EKONOMI DIGITAL DAN PERKEMBANGAN TEKNOLOGI TERHADAP KINERJA PENJUALAN HOME INDUSTRI TERASI KOTA LANGSA - Imam Malik; Murni Murni (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The negative impact has spread to Langsa City on the sale of shrimp paste, in which it is not ready to face the outside world with technological developments. The development of technology is expected to help Small and Medium Enterprises (MSMEs) to more easily obtain market information and facilitate connections between market participants. The digital economy has both positive and negative impacts on the Indonesian economy. Sales performance must be supported by technology that facilitates sales or production systems on a large scale to increase sales. The technique of collecting data is through a questionnaire form. The scale used in the preparation of the questionnaire is a Likert scale. Methods of data analysis using multiple linear regression techniques. Before testing the data with multiple linear regression, the validity, reliability and classical assumptions were first tested which consisted of normality test, multicollinearity and heteroscedasticity test, partial t test and simultaneous test.the results obtained the conclusion that the digital economy has a positive and significant effect on sales performance. While technological developments do not have a positive and significant effect on sales performance. It can be explained that the development of digital marketing has a tremendous impact and production technology.